SIGNIFICANCE OF PRAGMATICS WITHIN SLA INSTRUCTION WITH FOCUS ON THE SPEECH ACT OF REQUESTS - Zardaryan, Edgar (Armenian Folia Anglistika, 2023)
This comprehensive report illuminates the profound significance of pragmatics within the realm of Second Language Acquisition (SLA), with a specific emphasis on the speech act of requests. By examining studies rooted in Speech Act Theory, we can further investigate the critical role of pragmatic competence within the ESL/EFL classroom setting. This paper centralizes student perceptions of pragmatics while taking into consideration both cross-linguistic and extra-linguistic factors. Furthermore, the report will present novel innovative pedagogical practices that seamlessly integrate Task-Based Learning Theory and Data-Driven Learning, facilitating the effective enhancement of pragmatic language skills.
Keywords: Second Language Acquisition; Speech Act Theory; Pragmatic competence; ESL/EFL; Task-Based Learning Theory; Data-Driven Learning; Communicative Approach